Analysis Of Channels, Margins, Farmer’s Share And Marketing Efficiency Of Rice - Wandira, Ayu; Andani, Apri; Yuristia, Rahmi; Yulianti, Astrina (JURNAL AGRIBISAINS, 2025)
The rice marketing system in Bengkulu City faces the challenges of long distribution channels and price fluctuations. Marketing efficiency, which is influenced by proper channel selection, plays a crucial role in maximizing farmers’ profits and minimizing marketing costs. Bengkulu City, despite experiencing an increase in rice production throughout 2023, must still be balanced with distribution efficiency to optimize the economic value received by farmers and keep prices affordable for consumers. This study aims to analyze the channels, marketing margins, farmer’s share, and marketing efficiency of rice. The research was conducted in Rawa Makmur Permai and Dusun Besar with accidental sampling method for farmers (71 people) and snowball sampling for marketing institutions (4 people). Results showed that 87% of farmers sold directly to collectors. The highest marketing margin is Rp.17,500 and the lowest marketing margin is Rp.14,500. Rice marketing channels in Bengkulu City are inefficient based on farmer’s share criteria with an average percentage of 47.75% < 70%, based on marketing efficiency criteria, rice marketing channels in Bengkulu City are categorized as efficient, because the EP value < 1% (0.50 < 1). Recommendations include marketing digitalization, strengthening cooperatives, and training to improve farmers’ competitiveness.